Effect of palm oil fuel ash (POFA) fineness on the mechanical properties of concrete - Lau, Jeffrey Yong Lian (Universiti Malaysia Sarawak (UNIMAS), 2014)
palm oil industry in Malaysia is well known as the most important agricultural industry. Million tonnes of palm oil fuel ash (POF A) is being generated every year without any profitable return. POF A has the potential to be used as recycle materials due to their pozzolanic behaviour. Thus, this research project presents the effect of palm oil fuel ash (POFA) on the mechanical properties of concrete In this research project, POF A was used as supplementary cementing material to replace cement in concrete production. This is because POF A contains siliceous composition which produces a stronger and denser concrete. Three different fineness of POFA (passing through 38j.Ull, 63j.Ull and 75j.Ull) were used to replace ordinary portland cement at 15% by weight of cement throughout this research project. In the mix proportion, a mix design ratio of 1: 1.15:2.95 (Cement: Fine Aggregate: Coarse Aggregate) in term of weight of the components was constant for all mixtures. In this research project, three laboratory experimentai tests were carried out namely slump test, compressive strength test and splitting tensile strength test. The strength of POF A concrete are tested and determined at 3, 7 and 28 days. Workability in terms of slump and strength properties of POF A concrete were studied and compared with control specimen as well. The study revealed that POF A fmeness had significant effect on the workability and strength of concrete. The test results indicated th~, higher slump with higher fineness than those with lower fineness. Compressive strength and splitting tensile strength was found to increase with the increase of POFA fineness. Consequently, it was found that POFA concrete produces lower strength than OPC concrete